Đặt S = 2.22 + 3.23 + 4.24 + ... + (n - 1).2n - 1 + n.2n
<=> S = 2S - S = (2.23 + 3.24 + 4.25 + .... + (n - 1).2n + n. 2n + 1) - (2.22 + 3.23 + 4.24 + ... + (n - 1).2n - 1 + n.2n)
S = (2.23 - 3.23) + (3.24 - 4.24) + (4.25 - 5.25) + .... + [(n - 1).2n - n.2n] + n.2n + 1 - 2.22
= -(23 + 24 + 25 + ... + 2n) + n.2n + 1 - 8
Đặt A = 23 + 24 + 25 + ... + 2n
<=> 2A - A = (24 + 25 + 26 + ... + 2n + 1) - (23 + 24 + 25 + ... + 2n)
<=> A = 2n + 1 - 23
Khi đó S = - 2n - 1 + 23 + n.2n - 1 - 8
= 2n - 1.(n - 1) = 2n + 34
=> n - 1 = 2n + 34 : 2n - 1
=> n - 1 = 2n + 34 - n + 1
=> n - 1 = 235
=> n = 235 + 1
Cường xo tính lại kết quả của Xyz mà cũng làm